2013
DOI: 10.2337/db12-0406
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Type 2 Diabetes in Indians Identifies a New Susceptibility Locus at 2q21

Abstract: Indians undergoing socioeconomic and lifestyle transitions will be maximally affected by epidemic of type 2 diabetes (T2D). We conducted a two-stage genome-wide association study of T2D in 12,535 Indians, a less explored but high-risk group. We identified a new type 2 diabetes–associated locus at 2q21, with the lead signal being rs6723108 (odds ratio 1.31; P = 3.32 × 10−9). Imputation analysis refined the signal to rs998451 (odds ratio 1.56; P = 6.3 × 10−12) within TMEM163 that encodes a probable vesicular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 44 publications
2
117
2
Order By: Relevance
“…Genome-wide association studies (GWASs) and subsequent meta-analyses have identified >56 susceptibility loci for type 2 DM (3)(4)(5)(6)(7)(8)(9)(10)(11). However, these susceptibility loci have been identified predominantly in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) and subsequent meta-analyses have identified >56 susceptibility loci for type 2 DM (3)(4)(5)(6)(7)(8)(9)(10)(11). However, these susceptibility loci have been identified predominantly in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47]. The majority of SNPs that associated with T2D in one ethnic group showed some evidence of association in other ethnic groups as well.…”
Section: Gwas Imputation and Meta-analysis In Diverse Ethnic Groupsmentioning
confidence: 94%
“…These studies have provided strong evidence of an association of the genes involved in β-cell development, proliferation, function, and apoptosis [5][6][7][8][9][10][11][12][13]. Other associated genes are involved in glucose homeostasis [5,7,14], insulin secretion, resistance, and function [5,7,[12][13][14][15][16][17][18][19][20][21][22][23], membrane transporters [5,24], transcription factors (TFs) [25][26][27], and energy sensing and fat metabolism [7,8,10,12,24,[28][29][30].…”
Section: Candidate Genes and Genome-wide Studies: Delineating Susceptmentioning
confidence: 99%